A Multianalyte Assay Panel With Cell‐Bound Complement Activation Products Predicts Transition of Probable Lupus to American College of Rheumatology–Classified Lupus. Issue 2 (4th February 2021) - Ramsey‐Goldman, Rosalind; Alexander, Roberta Vezza; Conklin, John; Arriens, Cristina; Narain, Sonali; Massarotti, Elena M.; Wallace, Daniel J.; Collins, Christopher E.; Saxena, Amit; Putterman, Chaim; Brady, Kelley; Kalunian, Kenneth C.; et al.
Abstract : Objective: To evaluate the usefulness of biomarkers to predict the evolution of patients suspected of systemic lupus erythematosus (SLE), designated as probable SLE (pSLE), into classifiable SLE according to the American College of Rheumatology (ACR) classification criteria. Methods: Patients suspected of SLE were enrolled by lupus experts if they fulfilled three ACR criteria for SLE and were followed for approximately 1‐3 years to evaluate transition into ACR‐classifiable SLE. Individual cell‐bound complement activation products (CB‐CAPs), serum complement proteins (C3 and C4), and autoantibodies were measured by flow cytometry, turbidimetry, and enzyme‐linked immunosorbent assay, respectively. Blood levels of hydroxychloroquine (HCQ) were measured by mass spectrometry. A multianalyte assay panel (MAP), which includes CB‐CAPs, was also evaluated. A MAP of greater than 0.8 reflected the optimal cutoff for transition to SLE. Time to fulfillment of ACR criteria was evaluated by Kaplan‐Meier analysis and Cox proportional hazards model. Results: Of the 92 patients with pSLE enrolled, 74 had one or two follow‐up visits 9‐35 months after enrollment for a total of 128 follow‐up visits. Overall, 28 patients with pSLE (30.4%) transitioned to ACR‐classifiable SLE, including 16 (57%) in the first year and 12 (43%) afterwards. A MAP score of greater than 0.8 at enrollment predicted transition to classifiable SLE during the follow‐up period (hazard ratio = 2.72; P = 0.012), whereas individual biomarkers or fulfillment of Systemic Lupus International Collaborating Clinics criteria did not. HCQ therapy was not associated with the prevention of transition to SLE. Conclusion: Approximately one‐third of patients with pSLE transitioned within the study period. MAP of greater than 0.8 predicted disease evolution into classifiable SLE.